Acceptability of an intervention for contraceptive use among adolescents in an indigenous community in Mexico - Ramirez-Espinobarros, Yesenia (2024)
Introduction: pregnancy at an early age continues to be a public health problem due to the complications that can occur. Adolescents are a vulnerable group due to the transition stage, where practices such as the lack of contraceptives in sexual relations lead to unwanted pregnancy. Objective: to evaluate the acceptability of the Responsible Steps intervention designed for the use of contraceptives in adolescents in an indigenous community in Mexico. Material and methods: pilot trial with an experimental and control group, which included 84 adolescents of both sexes aged 12 to 19 years. Acceptability was evaluated through dropout rate, burden of participation and satisfaction with the intervention. Results: a dropout rate of 48% was obtained and 73% of the participants showed burden during their participation during the sessions. In terms of satisfaction, the scores increased as the sessions progressed. Conclusions: the study showed that the intervention was acceptable according to the satisfaction of the participants, however, the burden of participation was high and there were also losses during the study.